Capital femoral physeal dysplasia in cats submited to ostectomy of the femoral head and neck - Moi, Tryssia Scalon Magalhães [UNESP]; Pires, Marco Aurélio Molina; Yamauchi, Kelly Cristiane Ito; Dias, Luís Gustavo Gosuen Gonçalves [UNESP]; Minto, Bruno Watanabe [UNESP] (FapUNIFESP (SciELO), 2021)
This report described pathological fracture of the femoral head (physeal dysplasia) in four male cats (three mixed breed and one Bengal), with an average age of 16 months, treated by an ostectomy of the femoral head and neck. Three cats were neutered and one entire. All presented with mild intermittent lameness in the pelvic limbs. Displacement of the femoral epiphysis and resorption of the femoral neck were present and excision of the femoral head and remaining neck was performed in all cases. Hstological examination showed mild foci of compaction and trabecular fibrosis with deposition of fibrous connective tissue, permeated by granulation tissues, consistent with the original diagosis. Limb function improved in all patients from 2 to 4 weeks postoperatively. Diagnosis of physeal dysplasia is challenging and treatment is different from acute traumatic fractures. Femoral head and neck excision was considered a good alternative in these patients.
Displasia femoral capital em felinos submetidos a ostectomia da cabeça e colo femoral
Keywords: Colocefalectomy; Dysplasia; Epiphysiolysis; Ostectomy; Slipped capital femoral epiphysis